Kategoria aspektu w języku polskim i niemieckim. Analiza translatywna - Nadachewicz, Anna (Investigationes Linguisticae, 2007)
The category of aspect is usually viewed as an obligatory grammatical (morphological) verbal category existing in the Slavic, but not in the Germanic languages. This article considers possibilities of expressing aspectual meanings in German as one of the so-called aspectless languages. It presents a translative comparative analysis of the Polish novel ?Wysoki Zamek? by Stanisław Lem and it?s translation into German. It studies language means used for expressing aspect in the Polish text and their potential equivalents in the German translation. As shown in the analysis, Polish verbs are not the only carriers of aspectual meanings. As a result of complex bilateral relationships between aspect and Aktionsart (kind of action) some non-verbal means, e.g. adverbials, conjunctions and nouns being objects, also may be considered as indicators of aspectual meanings in Polish. This study argues for equivalent non-verbal means, semantics of verbs and verbal phrases as well as fixed syntagms being potential carriers of aspectual meanings in German as in a language with no morphological category of aspect.